Защита Гурова - Леонов Николай Иванович (Серия "Черная кошка", 1997)
Книга в суперобложке. Экземпляры: аб. ЦБ (2017.18.09) / Инвентарный номер: 3307 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Л47 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6